(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2015)
This manuscript chronicles the development of three graduate students as community engaged scholars, from the perspective of one of the students. With the support of the course instructor, a student (Thomas) and the instructor (Leah) discuss students’ development during their enrollment in a graduate course in community-engaged scholarship (CES) at the University of Guelph, a large comprehensive university in southwestern Ontario. Drawing from students’ reflection papers and progress reports, this article highlights students’ thoughts on communities’ perceptions of scholars; differences and similarities between community-engaged scholarship and more traditional forms of social science research; and challenges and opportunities of collaboration. Data highlighting students’ experiences with power relations, understandings of the need for adaptability within their respective partnerships, and acknowledgement of differences between community and academic roles in community-engaged research projects are also presented. Finally, the effects of large groups and imbalanced stakes on projects, and the influence of class-oriented timelines are discussed. The manuscript is written by, and from the perspective of Thomas Armitage, one of the students in the graduate course, in collaboration Leah Levac, the course instructor.